Positive plate and battery

By providing holes on the surface of the positive electrode active layer of the lithium-ion battery positive electrode sheet and forming a specific recessed structure, the problem that the positive electrode sheet in the prior art is difficult to take into account both the fast charging performance when improving the energy density, achieving both the high energy density and the fast charging performance, and extending the cycle life of the battery.

CN119833561APending Publication Date: 2025-04-15ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510037400.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

While increasing the energy density of existing lithium-ion battery positive electrodes, it is difficult to take into account fast charging performance, resulting in the problem of long charging time and incomplete capacity.

Method used

By providing holes on the surface of the positive electrode active layer, the wetting ability of the electrolyte to the positive electrode active material is improved, and a specific recess structure is formed in the holes, and the number of second particles is controlled to improve the cycle life and energy density of the battery.

Benefits of technology

It achieves the simultaneously improved the energy density and fast charging performance of the battery, extends the cycle life of the battery, and improves the structural stability of the positive electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833561A_ABST
    Figure CN119833561A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, in particular to a positive plate and a battery comprising the positive plate. The positive plate comprises a positive current collector and a positive active layer on the surface of at least one side of the positive current collector, the positive active layer comprises a positive active material, the positive active material comprises first particles and second particles, and the median diameter Dv50 of the first particles is larger than that of the second particles; holes are formed in the surface, far away from the positive electrode current collector, of the positive electrode active layer, each hole comprises a concave part, and the number n of the concave parts in each hole is larger than or equal to 2; the recesses contain the second particles, and the number of the second particles is 10 to 150 in the recesses of the optional pores. The positive plate provided by the invention can give consideration to both high energy density and fast charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application based on the invention with application number 2023111943925, application date September 15, 2023, and invention name “Positive electrode sheet and battery”. Technical Field

[0002] The present invention relates to the field of batteries, and in particular to a positive electrode sheet and a battery comprising the positive electrode sheet. Background Art

[0003] With the advent of the 5G era and the rapid development of lithium-ion battery technology, people have put forward higher requirements for the energy density, fast charging capability and charge and discharge rate of lithium-ion batteries. Fast-charging lithium-ion batteries with high energy density are the development trend of consumer lithium-ion batteries. However, the thickness of the positive electrode of lithium-ion batteries will increase with the increase of energy density, but there are problems such as long charging time and incomplete utilization of lithium-ion battery capacity.

[0004] Therefore, it is very important to find a battery that combines high energy density and fast charging performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem of the prior art that high energy density and fast charging cannot be taken into account at the same time, and to provide a positive electrode sheet and a battery comprising the positive electrode sheet. The battery including the positive electrode sheet of the present invention can take into account both high energy density and fast charging performance.

[0006] A first aspect of the present invention provides a positive electrode sheet, comprising a positive electrode collector and a positive electrode active layer on at least one side of the positive electrode collector, wherein the positive electrode active layer comprises a positive electrode active material, wherein the positive electrode active material comprises a first particle and a second particle, wherein the median particle size Dv50 of the first particle is greater than the median particle size Dv50 of the second particle; the positive electrode active layer comprises holes on a surface away from the positive electrode collector, wherein the holes comprise recesses, and the number of the recesses in each hole is n≥2; the recesses comprise the second particles, and in any recess of the hole, the number of the second particles is 10-150.

[0007] A second aspect of the present invention provides a battery, comprising the positive electrode sheet described in the first aspect of the present invention.

[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0009] (1) The positive electrode sheet of the present invention is provided with holes on the surface of the positive electrode active layer, which can improve the wettability of the electrolyte to the positive electrode active material close to the positive electrode current collector, thereby improving the utilization rate of the positive electrode active material close to the positive electrode current collector, and improving the energy density and fast charging performance of the battery;

[0010] (2) The positive electrode sheet of the present invention is provided with holes on the surface of the positive electrode active layer, and the holes contain recesses. The recesses formed do not destroy the complete positive electrode active material particles, thereby ensuring the stability of the positive electrode active material structure and improving the cycle life of the battery; and the number of recesses in each hole is within a specific range. The recesses provide sites for lithium ions to embed and escape, which is beneficial to the embedding of lithium ions and the infiltration of electrolyte, and can further improve the cycle life of the battery; at the same time, controlling the number of second particles in the recesses can increase the contact area between the electrolyte and the positive electrode active material, improve the structural stability of the positive electrode sheet, and thus improve the energy density of the battery.

[0011] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Shown is a schematic cross-sectional view of a positive electrode sheet in an example of the present invention.

[0013] Figure 2 Shown is a scanning electron microscope (SEM) image of a positive electrode sheet in an example of the present invention.

[0014] Figure 3 Shown is a scanning electron microscope (SEM) image of a local cross section of a positive electrode sheet in an example of the present invention.

[0015] Figure 4 Shown is a local scanning electron microscope (SEM) image of a positive electrode sheet in an example of the present invention.

[0016] Figure 5 Shown is a scanning electron microscope (SEM) image of a positive electrode sheet in an example of the present invention.

[0017] Figure 6 Shown is a scanning electron microscope (SEM) image of a cross section of a positive electrode sheet in an example of the present invention. DETAILED DESCRIPTION

[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0019] A first aspect of the present invention provides a positive electrode sheet, which may include a positive electrode current collector and a positive electrode active layer on at least one side of the positive electrode current collector. Figure 1 FIG. 1 is a schematic cross-sectional view of a positive electrode sheet in an embodiment of the present invention, wherein Figure 1 (a) The positive electrode active layer is set on one side; Figure 1 (b) and Figure 1 (c) is the case where the positive electrode active layer is set on both sides. Figure 1 In (a), the positive electrode sheet includes a positive electrode current collector 1 and a positive electrode active layer 2 on one side surface of the positive electrode current collector 1; Figure 1 (b) and Figure 1 In (c), the positive electrode sheet includes a positive electrode current collector 1 and a positive electrode active layer 2 on both sides of the positive electrode current collector 1 .

[0020] In the present invention, the positive electrode active layer may include a positive electrode active material, and the positive electrode active material may include first particles and second particles, wherein a median particle size Dv50 of the first particles is greater than a median particle size Dv50 of the second particles.

[0021] The inventors of the present invention have found that by using first particles and second particles with different median particle sizes Dv50 in combination, the compaction density of the positive electrode sheet can be increased, thereby increasing the energy density of the battery.

[0022] In the present invention, the positive electrode active layer may contain pores on a surface away from the positive electrode current collector.

[0023] In the present invention, the hole may contain recesses, and the number n of the recesses in each hole is ≥2 (for example, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 or 35). The recess may contain the second particles, and the number of the second particles in the recess of the optional hole may be 10-150 (e.g., 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145 or 150).

[0024] When the surface density of the positive electrode is greater than or equal to 10 mg / cm 2During the charge and discharge cycle, the positive electrode sheet is too thick, which makes the electrolyte's infiltration of the positive electrode active material close to the positive electrode collector worse, and the transmission distance of lithium ions is long, which makes the utilization rate of the positive electrode active material low, and finally leads to incomplete battery capacity. The inventors of the present invention have found that the provision of holes on the outer surface of the positive electrode active layer can effectively improve the electrolyte's infiltration of the positive electrode active material close to the positive electrode collector, shorten the transmission distance of lithium ions, and improve the effective utilization rate of the positive electrode active material, thereby simultaneously improving the energy density and rate performance of the battery. The inventors of the present invention have further found that when the holes provided on the outer surface of the positive electrode active layer contain recesses, and the number of recesses in each hole is within a specific range, the cycle life of the battery can be improved. The reason may be that the above-mentioned concave portion is generally caused by the absence of the first particle in the positive electrode active layer, and the first particle includes the positive electrode active material. The absence of the first particle is the absence of a complete positive electrode active material particle, and no new positive electrode active material interface will be formed, which can avoid the occurrence of side reactions, thereby effectively improving the cycle life of the battery; on the contrary, the absence of the above-mentioned concave portion indicates that the complete positive electrode active material particles are broken, resulting in the new surface inside the particles being exposed to the outside and in contact with the electrolyte, resulting in the occurrence of side reactions, consumption of electrolyte, and deterioration of the cycle life. The following is an example of lithium cobalt oxide particles with modified positive electrode active materials (the modification includes coating the surface of the positive electrode active material and bulk doping the positive electrode active material):

[0025] This specific concave portion will not destroy the coating layer on the surface of the lithium cobalt oxide particles. The function of the coating layer is to reduce the contact between the active sites on the surface of the lithium cobalt oxide particles and the electrolyte, thereby reducing side reactions. On the contrary, the absence of the above-mentioned specific concave portion will destroy the coating layer on the surface of the lithium cobalt oxide particles, increase the contact between the surface of the lithium cobalt oxide particles and the electrolyte, and increase the risk of side reactions. This specific concave portion will not destroy the bulk doping either. The function of doping is to stabilize the surface structure and prevent the entire particle from collapsing during the charge and discharge process. On the contrary, the absence of the above-mentioned specific concave portion will destroy the bulk doping and weaken the structural stability of the lithium cobalt oxide particles, thereby affecting the cycle life of the battery. Therefore, the specific concave portion can reduce the side reactions between the positive electrode sheet and the electrolyte, and effectively improve the high-temperature cycle life of the battery.

[0026] At the same time, by controlling the number of second particles in the recess, the contact area between the electrolyte and the second particles can be increased, the contact sites can be increased, and the wetting effect of the electrolyte can be improved; in addition, the recess itself also increases the wettability of the electrolyte. The two work together to significantly improve the wetting effect of the electrolyte.

[0027] In one example, n is 2-20.

[0028] In one embodiment, n is 5-10.

[0029] In the present invention, the diameter of the recess may be 5 μm-55 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or 55 μm.

[0030] In the present invention, the depth of the recess may be 5 μm-55 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or 55 μm.

[0031] In one example, the diameter of the recess is 10 μm-45 μm.

[0032] In one example, the depth of the recess is 10 μm-45 μm.

[0033] In the present invention, n can be obtained by testing by conventional testing methods in the art, such as by observation through a scanning electron microscope (SEM). The diameter of the concave portion can be obtained by testing by conventional testing methods in the art, such as by measurement through SEM. The depth of the concave portion can be obtained by testing by conventional testing methods in the art, such as by testing the depth of the concave portion through a 3D profilometer.

[0034] In the present invention, the diameter of the recess has the conventional meaning in this field. When the recess is a regular sphere, the diameter of the recess is the diameter of the sphere; when the recess is an irregular sphere, the diameter of the recess is the diameter of the circumscribed sphere of the irregular sphere.

[0035] In the present invention, the depth of the concave portion refers to the maximum value of the vertical distance from the bottom of the concave portion to the outer surface of the positive electrode active layer.

[0036] In the present invention, the pores can be obtained by laser pore making.

[0037] In the present invention, a conductive agent and / or a binder is included between the second particles and the recessed portion, and a conductive agent and / or a binder is included between the second particles.

[0038] In the present invention, the hole may further include a convex portion. The convex portion is formed at the junction of two adjacent concave portions. The convex portion may include the second particle.

[0039] In the present invention, the average particle size of the second particles may be 1 μm-10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0040] In one example, the average particle size of the second particles is 2 μm-8 μm.

[0041] In one example, the average particle size of the second particles is 3 μm-7 μm.

[0042] In the present invention, the number of the second particles contained in the protrusion is 10-150, for example, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145 or 150.

[0043] In the present invention, the average particle size of the second particles can be measured by a conventional test method in the art, such as by SEM. The number of the second particles in the concave portion of each of the holes and the number of the second particles contained in the convex portion can be measured by a conventional test method in the art, such as by SEM.

[0044] In the present invention, the particle sizes Dv50 and Dv90 of the positive electrode active material and the depth H of the pores may satisfy the following relationship: 15×Dv50 / Dv90 <H<(10×Dv90 / Dv50)+28。

[0045] The inventors of the present invention have found that when the particle size Dv50 and Dv90 of the positive electrode active material and the depth H of the hole meet a specific relationship, the rate performance and cycle life of the battery can be further improved. When H is too small, the electrolyte does not wet the positive electrode active material close to the current collector well, affecting the rate performance of the battery; and when H is too large, it is necessary to increase the energy to form the hole. At this time, excessive energy may damage the complete positive electrode active material particles, thereby affecting the service life of the battery. When the particle size of the positive electrode active material and the depth H of the hole meet the above relationship, the laser acts on the positive electrode active material particles, and the energy absorbed by the particle surface can just break the binder between the particles, causing it to fail and fall off, thereby improving the service life of the battery while ensuring the rate performance of the battery.

[0046] In the present invention, the particle sizes Dv50 and Dv90 of the positive electrode active material can be measured by conventional testing methods in the art, such as by a laser particle size analyzer.

[0047] In the present invention, 11 μm ≤ Dv50 ≤ 20 μm, for example, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.

[0048] In the present invention, 25 μm ≤ Dv90 ≤ 33 μm, for example, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm or 33 μm.

[0049] The inventors of the present invention have discovered that when the particle sizes Dv50 and Dv90 of the positive electrode active material are within a specific range, the combination of its particles can increase the gaps between the particles, thereby improving the wetting effect of the electrolyte, increasing the active sites, and at the same time helping the electrolyte to form a CEI film on the surface of the recess, thereby protecting the positive electrode sheet; when the particle sizes Dv50 and Dv90 of the positive electrode active material are within a specific range, the recess can be formed without destroying the complete positive electrode active material particles, so that no new active material interface is formed, thereby ensuring the stability of the positive electrode active material structure and improving the cycle life of the battery.

[0050] In the present invention, the depth H of the hole may be the maximum value of the depth of the recess.

[0051] In the present invention, 5 μm ≤ H ≤ 55 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or 55 μm.

[0052] In one example, 10 μm ≤ H ≤ 47 μm.

[0053] like Figure 2 The figure shows a scanning electron microscope (SEM) image of a positive electrode sheet in an embodiment of the present invention. Figure 3 The figure shows a partial cross-section scanning electron microscope (SEM) image of a positive electrode sheet in an example of the present invention. Figure 2 and Figure 3 It can be seen that the outer surface of the positive electrode active layer has holes. Figure 4 FIG. 1 is a local scanning electron microscope (SEM) image of a positive electrode sheet in an example of the present invention, wherein the portion framed by a black dotted line in the image is a concave portion. Figure 4 It can be seen from the figure that the number n of the recesses of the hole is 7, and the diameter of the recesses is 10 μm-30 μm.

[0054] In the present invention, during the pore formation process, the projection shape of the formed pores on the positive electrode active layer may include irregular curved polygons. Figure 5 The figure shows a scanning electron microscope (SEM) image of a positive electrode sheet in an example of the present invention. Figure 5 It can be seen that the shape of the projection of the hole on the positive electrode active layer is an irregular curved polygon.

[0055] In the present invention, the straight-line distance between any two points on the projection of the hole on the surface of the positive electrode active layer is L, where 0 < L ≤ 160 μm, such as 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm or 160 μm.

[0056] In one example, 0 < L ≤ 135 μm.

[0057] In one example, 0 < L ≤ 115 μm.

[0058] In the present invention, the aperture diameter of the hole on the side away from the positive electrode current collector is D1, and the aperture diameter of the hole on the side close to the positive electrode current collector is D2, where D1 > D2.

[0059] In the present invention, the aperture diameter of the hole has its conventional meaning in the art. Generally, when the shape of the projection of the hole on the positive electrode coating is a "regular circle", the aperture diameter of the hole is the diameter of this regular circle; when the shape of the projection of the hole on the positive electrode coating is not a "regular circle" (such as an ellipse or an irregular curved polygon), the aperture diameter of the hole is the diameter of an equivalent circle with the same area as this non-"regular circle".

[0060] In the present invention, the spacing between the holes can be 10 μm - 970 μm, such as 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm or 970 μm.

[0061] In one example, the spacing between the holes is 50 μm - 600 μm.

[0062] In one example, the spacing between the holes is 100 μm - 550 μm.

[0063] In the present invention, the spacing between the holes refers to the shortest distance between the edges of two adjacent holes.

[0064] In the present invention, the areal density of the positive electrode sheet can be 10 mg / cm 2 - 35 mg / cm 2 For example, 10 mg / cm 2、15mg / cm 2 , 20mg / cm 2 , 25mg / cm 2 、30mg / cm 2 or 35mg / cm 2 .

[0065] The inventors of the present invention have discovered that when the surface density of the positive electrode sheet is within a specific range, the energy density of the battery can be improved; at the same time, providing holes on the outer surface of the positive electrode active layer can improve the wettability of the electrolyte to the positive electrode active material close to the positive electrode current collector, shorten the transmission distance of lithium ions, and improve the effective utilization rate of the positive electrode active material, thereby further improving the energy density of the battery.

[0066] In the present invention, the thickness of the positive electrode active layer may be 30 μm-110 μm, for example, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or 110 μm.

[0067] In the present invention, the depth of the pores is smaller than the thickness of the positive electrode active layer.

[0068] In one example, the difference between the thickness of the positive electrode active layer and the depth of the pores is ≤5 μm.

[0069] In the present invention, the thickness of the positive electrode active layer refers to the thickness of the positive electrode active layer on one side.

[0070] In the present invention, the periphery of the hole may include protrusions, and the height of the protrusions may be 0-5 μm (eg, 0 μm, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm).

[0071] In one example, the height of the protrusion is 0 μm-0.2 μm.

[0072] The inventors of the present invention have found that when the height of the protrusion is within a specific range, the contact area between the positive electrode sheet and the electrolyte can be increased, thereby improving the reaction rate and charge transfer efficiency of the battery; at the same time, the activity of the positive electrode active material can be ensured, thereby improving the cycle stability and energy density of the battery.

[0073] In the present invention, the height of the protrusion can be measured by conventional means in the art, such as by a 3D profilometer.

[0074] In the present invention, the positive electrode active layer may include N coating layers, wherein N≥1 (eg, N=1, 2, 3, 4, 5, 6, 7 or 8).

[0075] In one example, the positive electrode active layer is a single layer.

[0076] In one example, the positive electrode active layer includes a first coating layer and a second coating layer sequentially stacked along a thickness direction of the positive electrode sheet.

[0077] In one example, the positive electrode active layer includes a first coating layer, a second coating layer, and a third coating layer stacked in sequence along the thickness direction of the positive electrode sheet.

[0078] In the present invention, the N-layer coating can be obtained by drying the same positive electrode active layer slurry, or by drying different positive electrode active layer slurries.

[0079] In the present invention, the positive electrode sheet may further include a ceramic layer, and the ceramic layer may be located on the outer surface of the positive electrode active layer. Figure 6 The figure shows a scanning electron microscope (SEM) image of a cross section of a positive electrode sheet in an example of the present invention. It can be seen from the figure that the portion framed by the dotted square is the ceramic layer, and the portion framed by the dotted circle is the hole. The ceramic layer is located on the outer surface of the positive electrode active layer, and the ceramic layer covers the surface of the hole.

[0080] The inventors of the present invention discovered that when the outer surface of the positive electrode active layer includes a ceramic layer, the ceramic layer can form a closed structure with the pores on the outer surface of the positive electrode active layer. The closed structure is similar to a liquid storage tank, which is conducive to storing electrolyte and infiltrating the positive electrode active material. In addition, the ceramic layer has liquid storage capacity and can be tightly attached to the pore wall to increase the liquid storage capacity at this position. The ceramic layer can also improve the safety of the battery.

[0081] In the present invention, the thickness of the ceramic layer may be 0.3 μm-3 μm, for example, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm.

[0082] In the present invention, the ceramic layer may include ceramic particles. The median particle size Dv50 of the ceramic particles may be 1 nm-3 μm, for example, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 2 μm or 3 μm.

[0083] The inventors of the present invention have found that when the median particle size Dv50 of the ceramic particles is within a specific range, it can provide more channels and paths for the transmission of lithium ions, which is conducive to the rapid transmission of lithium ions, absorbs more electrolyte, increases the battery electrolyte retention, and extends the battery cycle life.

[0084] In the present invention, the ceramic particles may include at least one of boehmite, silica, magnesium oxide, aluminum oxide, and aluminum hydroxide.

[0085] In the present invention, the positive electrode active layer may include a positive electrode active material, a binder and a conductive agent. The positive electrode active material may include at least one of lithium cobaltate, lithium nickel cobalt manganeseate, lithium nickel cobalt aluminumate, lithium nickel cobalt manganese aluminumate, lithium manganate, lithium nickel manganate, lithium nickelate, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate and lithium-rich manganese. The binder may include at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene butadiene latex, polytetrafluoroethylene and polyethylene oxide. The conductive agent may include at least one of conductive carbon black, acetylene black, ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes and carbon fiber.

[0086] In one example, the positive electrode active material includes a doping-modified and / or coating-modified positive electrode active material.

[0087] In the present invention, the positive electrode active material may include lithium cobalt oxide having a core-shell structure, the core of the core-shell structure includes lithium cobalt oxide doped with a metal element, wherein the doped metal element may include at least one of Al, Mg and M, M may include at least one of Ti, Zr, Y, La, Ni, Mn, Ce and W, and the shell of the core-shell structure includes a compound containing an element R, and R may include at least one of Al, Mg, Ti, Zr, Y, La, Ni and Mn.

[0088] In the present invention, the compound containing the element R may include at least one of an oxide, a fluoride and a phosphate of R.

[0089] In the present invention, the doping amount of the doped metal element Al can be 100ppm-18000ppm (for example, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm or 18000ppm), and the doping amount of the doped metal element Mg can be 100ppm-4500ppm (for example, 100ppm pm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 2000ppm, 3000ppm, 4000ppm or 4500ppm), the total doping amount of the doped metal elements Al, Mg and M can be 3000ppm-35000ppm (for example, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm, 20000ppm, 30000ppm or 35000ppm).

[0090] The inventors of the present invention have found that when the doping amount of the doped metal element is within a specific range, the stability of the positive electrode active material can be improved, and when holes are provided on the outer surface of the positive electrode active layer, a synergistic effect can be produced to further improve the stability of the positive electrode sheet, thereby improving the cycle life of the battery.

[0091] In one example, the doped metal element M includes at least one of Ti, Y and La.

[0092] In the present invention, based on the total weight of the lithium cobalt oxide with a core-shell structure, the content of the element R can be 0.01-5% by weight, for example, 0.01, 0.03, 0.05, 0.1, 0.15, 0.18, 0.25, 0.5, 0.7, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5% by weight.

[0093] The inventors of the present invention have discovered that when the content of element R in lithium cobalt oxide with a core-shell structure is within a specific range, the side reactions of the electrolyte can be effectively suppressed, and when holes are provided on the outer surface of the positive electrode active layer, a synergistic effect can be produced to further improve the stability of the positive electrode sheet and the electrolyte infiltration ability, thereby improving the cycle life of the battery.

[0094] In the present invention, the types and contents of the doped metal elements and the element R can be obtained by inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0095] In the present invention, based on the total weight of the positive electrode active layer, the content of the positive electrode active material can be 80-99.8 weight % (for example, 80, 85, 90, 95 or 99.8 weight %), the content of the conductive agent can be 0.1-10 weight % (for example, 10, 7.5, 5, 2.5 or 0.1 weight %), and the content of the binder can be 0.1-10 weight % (for example, 10, 7.5, 5, 2.5 or 0.1 weight %).

[0096] In one example, based on the total weight of the positive electrode active layer, the content of the positive electrode active material is 90-99.6% by weight, the content of the conductive agent is 0.2-5% by weight, and the content of the binder is 0.2-5% by weight.

[0097] The positive electrode sheet of the present invention can fully improve the problem that during the charge and discharge process of the battery with a large surface density, the thickness of the positive electrode sheet is too large, resulting in poor electrolyte infiltration of the positive electrode active material near the positive electrode collector, causing the lithium ion transmission distance to be too long, and the positive electrode active material cannot be effectively utilized, which ultimately leads to incomplete battery capacity. Furthermore, the surface of the positive electrode sheet of the present invention is covered with a ceramic layer, which can form a liquid storage tank with the holes on the positive electrode active layer, which is more conducive to storing electrolyte, infiltrating the positive electrode active material near the positive electrode sheet near the current collector, and improving the utilization rate of the positive electrode active material.

[0098] A second aspect of the present invention provides a battery, comprising the positive electrode sheet described in the first aspect of the present invention.

[0099] In the present invention, the components of the battery other than the positive electrode sheet (such as the negative electrode sheet, the separator and the electrolyte, etc.) can be conventionally selected in the art.

[0100] In one example, the battery further includes a negative electrode sheet, a separator and an electrolyte.

[0101] In the present invention, the negative electrode sheet may include a negative electrode current collector and a negative electrode active layer on at least one side of the negative electrode current collector, and the negative electrode active layer may include a negative electrode active material.

[0102] In the present invention, the negative electrode active material may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon, soft carbon, silicon, silicon oxygen, silicon carbon and silicon alloy.

[0103] In the present invention, the negative electrode active layer may further include a negative electrode conductive agent, a negative electrode binder and a thickener. The negative electrode conductive agent may include a conductive agent conventionally used in the art, such as at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes and carbon fiber. The negative electrode binder may be selected from a binder conventionally used in the art, such as at least one of polyvinylidene fluoride, styrene butadiene latex, polytetrafluoroethylene and polyethylene oxide. The thickener may be selected from a thickener conventionally used in the art, such as sodium carboxymethyl cellulose.

[0104] In the present invention, based on the total weight of the negative electrode active layer, the content of the negative electrode active material can be 70-99.7 weight % (for example, 70, 75, 80, 85, 90, 95 or 99.7 weight %), the content of the negative electrode conductor can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %), the content of the negative electrode binder can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %), and the content of the thickener can be 0.1-10 weight % (for example, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5 or 0.1 weight %).

[0105] In one example, based on the total weight of the negative electrode active layer, the content of the negative electrode active material is 85-99.4 wt %, the content of the negative electrode conductor is 0.2-5 wt %, the content of the negative electrode binder is 0.2-5 wt %, and the content of the thickener is 0.2-5 wt %.

[0106] In the present invention, the isolation membrane may include an isolation membrane conventionally used in the art, such as at least one of a polyethylene film and a polypropylene film; another example includes a base membrane and the ceramic layer arranged on both sides of the base membrane; another example includes a base membrane and a diaphragm ceramic layer and a polymer layer respectively arranged on both sides of the base membrane, wherein the diaphragm ceramic layer is arranged on one side of the positive electrode sheet (that is, the diaphragm ceramic layer is adjacent to the positive electrode sheet, and the polymer layer is adjacent to the negative electrode sheet).

[0107] The diaphragm ceramic layer may include ceramic particles. The ceramic particles may include at least one of boehmite, silicon dioxide, magnesium oxide, aluminum oxide and aluminum hydroxide. The base film may be a polyethylene film.

[0108] In the present invention, the ceramic layer on the outer surface of the positive electrode sheet can be obtained by directly coating the ceramic layer slurry on the outer surface of the positive electrode active layer and then drying it; or the diaphragm ceramic layer on the outer surface of the diaphragm can be formed on the outer surface of the positive electrode sheet by hot pressing, wherein there is no restriction on the parameters of the hot pressing, as long as the transfer of the diaphragm ceramic layer can be completed, for example, the temperature of the hot pressing is 80°C and the pressure is 1.1MPa.

[0109] In the present invention, the electrolyte may include a lithium salt and an organic solvent. The lithium salt may include at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium oxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, lithium bistrifluorosulfonyl imide and lithium bisfluorosulfonyl imide. The organic solvent may include at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC).

[0110] The electrolyte may further include an additive, and the additive may include at least one of fluoroethylene carbonate, vinylene carbonate, vinyl sulfate, methylene methanedisulfonate, propylene sultone, and succinic anhydride.

[0111] In one example, the battery is a lithium-ion battery.

[0112] The battery can be assembled in a conventional manner in the art.

[0113] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0114] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0115] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0116] The following examples are provided to illustrate the batteries of the present invention.

[0117] Example 1

[0118] Prepare the battery as follows:

[0119] (1) Preparation of negative electrode sheet

[0120] Artificial graphite, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose were mixed evenly in a mass ratio of 96.9:0.5:1.3:1.3, and deionized water was added to obtain a negative electrode slurry with a solid content of 45%. The negative electrode slurry was coated on a copper foil using a coating machine, dried at 100° C., and rolled and cut to obtain a negative electrode sheet.

[0121] (2) Preparation of positive electrode

[0122] Lithium cobalt oxide (doped with Al, Mg and Y in amounts of 8000ppm, 3000ppm and 8000ppm, respectively; the outer shell includes Zr with a Zr content of 1.7%), conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.2:1.5:1.3, and N-methylpyrrolidone (NMP) is added to obtain a positive electrode slurry with a solid content of 72%. The positive electrode slurry is coated on an aluminum foil using a coating machine, dried at 120°C, and heated to room temperature. The outer surface of the positive electrode active layer is perforated, wherein the parameters of the holes are shown in Table 1; aluminum oxide particles (median particle size Dv50 is 0.5 μm), methacrylic acid and sodium carboxymethyl cellulose are mixed in a mass ratio of 90:4:6, and NMP is added to prepare a ceramic layer slurry with a solid content of 20%, which is coated on the outer surface of the perforated positive electrode active layer with a gravure coater according to the thickness requirement; drying, rolling and slitting are performed to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is 23 mg / cm 2 The thickness of the positive electrode active layer is 60 μm.

[0123] (3) Preparation of batteries

[0124] The negative electrode sheet obtained in step (1), the positive electrode sheet obtained in step (2) and the isolation film (polyethylene film, thickness of 9 μm) were wound to form a core, wrapped with aluminum plastic film, baked to remove moisture, and then injected with electrolyte (propylene carbonate, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate were mixed in a weight ratio of 1:1:0.5:1, and 1 mol / L LiPF was added). 6 The mixture is uniformly mixed), and a battery is obtained by adopting a hot pressing process.

[0125] Examples 2-10 are carried out in reference to Example 1, except that n, the diameter of the recess, the depth of the recess, the number of second particles in the recess, H, the number of second particles in the protrusion, the average particle size of the second particles, Dv50 and Dv90 of the positive electrode active material, L, the spacing, the protrusion height, the presence or absence of a ceramic layer, and the thickness of the ceramic layer are changed, as shown in Table 1.

[0126] Table 1

[0127]

[0128]

[0129]

[0130] Embodiment 11

[0131] The method is carried out in accordance with Example 1, except that in step (2), the lithium cobalt oxide (the metal elements doped are Al, Mg and Y, and the doping amounts are 8000ppm, 3000ppm and 8000ppm respectively; the shell includes Zr, and the Zr content is 1.7%) is replaced with the same mass of lithium cobalt oxide that has not been doped or coated.

[0132] Comparative Example 1

[0133] The process is carried out in accordance with Example 1, except that the energy parameters of the punching are adjusted in step (2) to obtain n of 5-10, a diameter of the recess of 32 μm, a depth of the recess of 29 μm, and 170 second particles in the recess.

[0134] Comparative Example 2

[0135] The same process is carried out as in Example 1, except that the positive electrode sheet is not punched.

[0136] Test Case I

[0137] (1) Test of number of recesses

[0138] The punched positive electrode sheets (not coated with a ceramic layer) prepared in the examples and comparative examples were tested for the number of recesses. The specific test method is as follows:

[0139] Using SEM, 50 holes were randomly selected on the entire positive electrode sheet, and the number of recesses in each hole was observed. The results were recorded in Table 1. For example, in Example 1, n was 5-10, that is, among the 50 holes randomly selected on the positive electrode sheet of Example 1, the number of recesses in each hole was different, but all were within the range of 5-10 (including the two end point values).

[0140] (2) Diameter test of the concave part

[0141] The positive electrode sheets (not coated with a ceramic layer) after punching prepared in the examples and comparative examples were tested for the diameter of the concave portion. The specific test method is as follows:

[0142] Using SEM, 50 holes were randomly selected on the entire positive electrode sheet, and the diameter of the concave portion in each hole was measured. The average value was taken and the results were recorded in Table 1.

[0143] (3) Depth test of concave part

[0144] The punched positive electrode sheets (not coated with ceramic layer) prepared in the examples and comparative examples were tested for the depth of the concave portion. The specific test method is as follows:

[0145] Using a 3D profilometer, 50 holes were randomly selected on the entire positive electrode sheet, and the depth of the concave portion in each hole was measured. The average value was taken and the results were recorded in Table 1.

[0146] (4) Test of the number of second particles in the concave portion

[0147] The punched positive electrode sheets (not coated with a ceramic layer) prepared in the examples and comparative examples were tested for the number of second particles in the concave portion. The specific test method is as follows:

[0148] Using SEM, 10 holes were randomly selected on the entire positive electrode sheet, and the number of second particles in the concave portion of each hole was observed. The average value was taken and the results were recorded in Table 1.

[0149] (5) H test

[0150] The punched positive electrode sheets (not coated with ceramic layer) prepared in the examples and comparative examples were subjected to H test, and the specific test method was as follows:

[0151] Using a 3D profiler, 50 holes were randomly selected on the entire positive electrode sheet, the depth of each hole was measured, the average value was taken, and the results were recorded in Table 1.

[0152] (6) Test of the number of second particles in the convex part

[0153] The punched positive electrode sheets (not coated with a ceramic layer) prepared in the examples and comparative examples were tested for the number of second particles in the convex portion. The specific test method is as follows:

[0154] Using SEM, 10 holes were randomly selected on the entire positive electrode sheet, and the number of second particles in the convex portion of each hole was observed. The average value was taken and the results were recorded in Table 1.

[0155] (7) Average particle size test of the second particle

[0156] The punched positive electrode sheets (not coated with a ceramic layer) prepared in the examples and comparative examples were subjected to a second particle average particle size test, and the specific test method was as follows:

[0157] Using SEM, 10 holes were randomly selected on the entire positive electrode sheet, and the particle size of the second particles in each hole was observed and the average value was taken. The results are recorded in Table 1.

[0158] (8) Test of L

[0159] The punched positive electrode sheets (not coated with ceramic layer) prepared in the examples and comparative examples were tested for L. The specific test method is as follows:

[0160] Using SEM, 50 holes were randomly selected on the entire positive electrode sheet, and the maximum value of the straight-line distance between any two points on the projection of each hole on the positive electrode active layer was measured. The average value was taken and the results are recorded in Table 1.

[0161] (9) Hole spacing test

[0162] The hole spacing of the punched positive electrode sheets (not coated with a ceramic layer) prepared in the embodiment and the comparative example was tested, and the specific test method was as follows:

[0163] Using SEM, 50 holes were randomly selected on the entire positive electrode sheet, and the distance between two adjacent holes was measured. The minimum value was taken and the results were recorded in Table 1.

[0164] (10) Protrusion height test

[0165] The punched positive electrode sheets (not coated with a ceramic layer) prepared in the examples and comparative examples were tested for protrusion height, and the specific test method was as follows:

[0166] Using a 3D profilometer, 50 holes were randomly selected on the entire positive electrode sheet, and the height of the protrusion around each hole was measured. The maximum value was taken and the results were recorded in Table 1.

[0167] Test Case II

[0168] (1) Capacity retention rate

[0169] The batteries prepared in the examples and comparative examples were tested for capacity retention, and the specific test method is as follows:

[0170] At 25°C, 3.0C step charge / 0.7C discharge (the starting voltage of the charging process is 3.0V and the cut-off voltage is 4.5V; the starting voltage of the discharging process is 4.5V and the cut-off voltage is 3.0V) was performed for 800T cycle charge and discharge; the capacity retention rate was calculated as follows:

[0171] Capacity retention rate (%) = Ct / C0×100%,

[0172] The last discharge capacity is Ct, the first discharge capacity is C0, and the results are recorded in Table 2.

[0173] (2) Expansion rate

[0174] At 25°C, 3.0C step charge / 0.7C discharge (where the starting voltage of the charging process is 3.0V and the cut-off voltage is 4.5V; the starting voltage of the discharging process is 4.5V and the cut-off voltage is 3.0V) was performed for 800T cycle charge and discharge; the expansion rate was calculated as follows:

[0175] Expansion rate (%) = [(Ht / H0)-1] × 100%,

[0176] Among them, the battery thickness in the last fully charged state is Ht, and the battery thickness in the first fully charged state is H0. The results are recorded in Table 2.

[0177] (3) Charging speed

[0178] Perform 3.0C step charging at 25°C until the battery reaches 100% SOC (where the starting voltage of the charging process is 3.0V and the cut-off voltage is 4.5V), record the time required from 0% SOC to 100% SOC, and record the results in Table 2.

[0179] (4) Energy density

[0180] At 25°C, 3.0C step charging was performed until the battery reached 100% SOC (where the starting voltage of the charging process was 3.0V and the cut-off voltage was 4.5V), followed by 0.2C discharge to 3.0V (where the starting voltage of the discharge process was 4.5V and the cut-off voltage was 3.0V), and the discharge capacity was recorded. The calculation formula for energy density is as follows:

[0181] Energy density = 0.2C discharge capacity × voltage platform / battery volume,

[0182] Among them, the voltage platforms of different systems are different. The voltage platform of the embodiments of the present invention and the comparative example is 3.95V. The results are recorded in Table 2.

[0183] Table 2

[0184]

[0185]

[0186] As can be seen from Table 2, compared with the comparative example, the battery prepared by the positive electrode sheet of the present invention has improved the 800T capacity retention rate, reduced the 800T expansion rate, and shortened the charging time under the premise of ensuring a higher energy density. The battery including the positive electrode sheet of the present invention can take into account both high energy density and fast charging performance.

[0187] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode collector and a positive electrode active layer on at least one side of the positive electrode collector, wherein the positive electrode active layer includes a positive electrode active material; the positive electrode active layer contains holes on a surface away from the positive electrode collector, wherein the holes contain recesses, and the number of recesses in each hole is n≥2.

2. The positive electrode sheet according to claim 1, wherein: The positive electrode active material includes first particles and second particles, the median particle size Dv50 of the first particles is greater than the median particle size Dv50 of the second particles; the concave portion contains the second particles, and the number of the second particles in the concave portion of the optional hole is 10-150; and / or, n is 2-20; preferably 5-10; And / or, the diameter of the concave portion is 5 μm-55 μm; preferably 10 μm-45 μm; And / or, the depth of the recess is 5 μm-55 μm; preferably 10 μm-45 μm.

3. The positive electrode sheet according to claim 2, wherein: The average particle size of the second particles is 1 μm-10 μm; preferably 2 μm-8 μm; And / or, the hole further comprises a convex portion; the convex portion comprises the second particle; Preferably, the number of the second particles contained in the protrusion is 10-150.

4. The positive electrode sheet according to claim 1 or 2, wherein: The particle sizes Dv50 and Dv90 of the positive electrode active material and the depth H of the pores satisfy: 15×Dv50 / Dv90 <H<(10×Dv90 / Dv50)+28; and / or, 11 μm ≤ Dv50 ≤ 20 μm; and / or, 25 μm ≤ Dv90 ≤ 33 μm; And / or, the depth H of the hole is the maximum value of the depth of the recess, 5 μm≤H≤55 μm.

5. The positive electrode sheet according to claim 1 or 2, wherein: The straight-line distance between any two points on the projection of the hole on the surface of the positive electrode active layer is L, <L≤160μm; And / or, the pore size at the side away from the positive electrode current collector is D1, the pore size at the side close to the positive electrode current collector is D2, and D1>D2.

6. The positive electrode sheet according to claim 1 or 2, wherein: The spacing between the holes is 10 μm-970 μm; preferably 100 μm-550 μm; Preferably, the holes are obtained by laser pore making.

7. The positive electrode sheet according to claim 1 or 2, wherein: The depth of the pores is less than the thickness of the positive electrode active layer; And / or, the surface density of the positive electrode sheet is 10 mg / cm 2 -35mg / cm 2 ; And / or, the thickness of the positive electrode active layer is 30 μm-110 μm.

8. The positive electrode sheet according to claim 1 or 2, wherein: The periphery of the hole includes protrusions, and the height of the protrusions is 0 μm-5 μm, preferably 0 μm-0.2 μm.

9. The positive electrode sheet according to claim 1 or 2, wherein: The positive electrode sheet further comprises a ceramic layer, and the ceramic layer is located on the outer surface of the positive electrode active layer; Preferably, the ceramic layer covers the surface of the hole.

10. The positive electrode sheet according to claim 9, wherein: The ceramic layer includes ceramic particles; the ceramic particles include at least one of boehmite, silicon dioxide, magnesium oxide, aluminum oxide and aluminum hydroxide; And / or, the thickness of the ceramic layer is 0.3 μm-3 μm; And / or, the median particle size Dv50 of the ceramic particles is 1 nm-3 μm.

11. The positive electrode sheet according to claim 1 or 2, wherein: The positive electrode active material includes lithium cobalt oxide having a core-shell structure; Preferably, the core of the core-shell structure comprises lithium cobalt oxide doped with metal elements, wherein the doped metal element comprises at least one of Al, Mg and M, and M comprises at least one of Ti, Zr, Y, La, Ni, Mn, Ce and W; Preferably, the shell of the core-shell structure comprises a compound containing an element R, and R comprises at least one of Al, Mg, Ti, Zr, Y, La, Ni and Mn; Preferably, the doping amount of the doped metal element Al is 100ppm-18000ppm; the doping amount of the doped metal element Mg is 100ppm-4500ppm; the total doping amount of the doped metal elements Al, Mg and M is 3000ppm-35000ppm; Preferably, based on the total weight of the lithium cobalt oxide having a core-shell structure, the content of the element R is 0.01-5 wt %.

12. A battery, characterized in that: The battery comprises the positive electrode sheet according to any one of claims 1 to 11; Preferably, the battery is a lithium-ion battery.